FISHING ACTIVITIES AND FISHERMEN INCOME IN RANAU LAKE, SOUTH SUMATRA - Dina Muthmainah; Subagdja Subagdja; Makri Makri; Dwi Atminarso; Safran Makmur (Indonesian Fisheries Research Journal, 2015)
Fish resources contribute to the socio-economic development for people who live surrounding the waters. The fishermen of Ranau Lake, South Ogan Komering Ulu Regency, South Sumatra Province and West Lampung Regency, Lampung Province are the prime stakeholder and direct interest in fish resources, because they depend on it for their livelihoods or they are directly involved in its exploitation in some ways. However, to well manage these resources, it needs data and information about fish utilization and fishing activity. The objectives of this work are to assess fishing activities such as the fishing craft and gears, catch composition, fish yield, catch per unit of effort (CPUE) and to estimate the fihermen income with economical parameter such as cost and price. Field surveys were conducted from February to November 2014. Fishing activities data were collected from field survey and interview. The results showed that fish resources utilization in Ranau Lake was categorized as traditional and small scale fisheries using different selective fishing gears such gillnet, harpoon, net trap and basket trap with the fish catch in average of 696.66 g/day; 205.03 g/day; 1.584.06 g/day and 123.67 g/day, respectively. Fisherman income (IDR 2,163,300) means the fishermen in Ranau Lake reach standard Indonesian welfare.